2020
DOI: 10.1371/journal.pone.0233521
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of temporal summation, thermal and pressure pain thresholds in a healthy cohort and musculoskeletal trauma population

Abstract: Traumatic injuries affect approximately 978 million people worldwide with 56.2 million requiring inpatient care. Quantitative sensory testing (QST) can be useful in predicting outcome following trauma, however the reliability of multiple QST including temporal summation (TS), heat and cold pain thresholds (HPT, CPT) and pressure pain thresholds (PPT) is unknown. We assessed intra (between day) and inter-rater (within day) reliability of QST in asymptomatic participants (n = 21), and inter-rater (within day) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…The average temperature over three trials was calculated for the determination of HPT. Given the nature of the study, we focused our thermal procedures on HPT, which is thought to have better intra- and inter-rater reliability and less variability over time relative to other QST measures, to avoid as much as possible confounding effects of time between visits ( 59 , 60 ). Moreover, since our SRPS procedure is based on heat, we thought that HTP was the most adequate outcome to assess intervention changes.…”
Section: Methodsmentioning
confidence: 99%
“…The average temperature over three trials was calculated for the determination of HPT. Given the nature of the study, we focused our thermal procedures on HPT, which is thought to have better intra- and inter-rater reliability and less variability over time relative to other QST measures, to avoid as much as possible confounding effects of time between visits ( 59 , 60 ). Moreover, since our SRPS procedure is based on heat, we thought that HTP was the most adequate outcome to assess intervention changes.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the reliability of the QST in other painful conditions, some studies have investigated orofacial pain 23 , knee osteoarthritis 24 , and musculoskeletal traumatic injury 25 . Our results found the ICC values similar to the ones in the aforementioned studies, indicating a pattern of error in the measurements performed with the QST, regardless of the population with pain studied.…”
Section: Discussionmentioning
confidence: 99%
“…Middlebrook et al 25 measured the inter-rater reliability of the QST in the assessment of individuals with traumatic musculoskeletal injury and found the ICC values ranging from 0.57 to 0.94. Our study identified less variation of ICC in the measurements of the thermal pain threshold; however, our sample consisted of patients with chronic pain (>3 months of pain).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the specificity of the observed differences in a given pain modality should be assessed using withinsubject designs including quantitative sensory testing across multiple pain modalities (e.g. [35,36]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, future studies should investigate differences between sport expertise in nociceptive flexion reflex (R-III) which is considered as an index of spinal nociception [39]. Tests of central pain summation (e.g., [16,36,40]) or other pain modulation tests, such as heterotopic noxious counter-stimulation (conditioned pain modulation) [16], could be used to assess the efficacy of central pain regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%